The Association of Thyroid Disease and Oral Lichen Planus: A Literature Review and Meta-analysis - Li, Dan; Li, Jin; Li, Chunlei; Chen, Qianming; Hua, Hong (Frontiers in Endocrinology, 2017)
Background. The objective of this study was to systemically evaluate the association between oral lichen planus (OLP) and thyroid disease. Method. Eleven electronic databases were searched for any clinical study published up until August 2016 that explored an association between OLP and thyroid disease, complemented with manual searching. The titles and abstracts of all studies identified from the electronic searches were then assessed independently to determine inclusion of the study. The population of interest was patients with OLP, and the exposure was the presence of thyroid disease in OLP patients . Statistical analyses were conducted using Review Manager 5.2. The odds ratios (OR) and 95% confidence intervals (CIs) were calculated to evaluate the association between OLP and thyroid disease. Results. Eight studies were included for review, and of these, four case-control studies were included in the final meta-analysis. The mean Newcastle–Ottawa Scale score evaluating the methodological quality of the four studies was 6.5. The OR was 2.10 (95% CI: 1.47–3.01), indicating a statistically significant difference in the prevalence of thyroid disease between the OLP and control groups. Heterogeneity was satisfactory (I² = 0%, < 25%). An approximately symmetrical funnel plot suggested no obvious publication bias. Two articles showed a higher correlation between OLP and hypothyroidism (OR 1.83, 95% CI: 1.16–2.89), with satisfactory heterogeneity (I² = 0%, < 25%). Conclusion. This meta-analysis indicated a significantly high prevalence of thyroid disease among OLP patients compared with controls, suggesting that routine screening for thyroid disease could be beneficial to OLP patients. However, due to the small number of studies included, further studies are needed to confirm the results.